Proliferation of embryogenic callus of Satoimo taro (Colocasia esculenta var. antiquorum) in culture media with various levels of sucrose and gelling agent - HANI FITRIANI; PRAMESTI DWI ARYANINGRUM; N. SRI HARTATI (Nusantara Bioscience, 2016)
Abstract. Fitriani H, Aryaningrum PD, Hartati NS. 2016. Proliferation of embryogenic callus of Satoimo taro (Colocasia esculenta var. antiquorum) in culture media with various level of sucrose and gelling agent. Nusantara Bioscience 8: 316-320. Satoimo taro (Colocasia esculenta var. antiquorum) is one of the promising varieties of taro which have potentially high value to cultivate. Tissue culture or in-vitro culture considers an economically useful technique to mass propagates this variety of taro. The research was conducted to figuring out the optimum media for proliferation success of embryogenic callus of Satoimo. The explants used embryogenic callus of 12-months-old storage materials obtained from the previous study. Proliferation media include a basal half-strength MS salt (Murashige and Skoog) enriched with of 0.1 mg/L TDZ, 0.05 mg/L 2.4 D, and 100 mg/L L-glutamine. Adding to the basal media, we set the treatments by combining two factors i.e. Sucrose with three levels of concentration i.e. 3, 4, and 5% which cross-tabulated with three gelling agents, i.e., Agarose, Phytagel, and Gerlite. The research parameters included the percentage of callus diameter growth, the color and callus discoloration, and the structure of callus. The data recorded periodically every 7 d in one month. Data were analyzed using analysis of variance and followed by Duncan Multiple Range Test (DMRT) to determine the significant difference (p<0.05) among the treatments. The result revealed that the callus diameter growth has the greatest percentage at medium with a combination of Phytagel and sucrose 4%. The Micro-agar enhanced the presence of callus with yellow color. Phytagel combined with a high percentage of sucrose (5%) indicated browning properties of callus. Gelrite causes the callus with discoloration appearance (white).